The Nature of Law Enforcement of Illegal Fishing in Indonesia After The Establishment of The Employment Law - Muhammad Fauzi Ramadhan; Said, Muhammad Fachri; Syah, Syawal Amirul (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
This research aims to analyze and find out the reality of the enforcement of illegal fishing law in Indonesia as well as the enforcement of illegal fisheries law in indonesia after the introduction of the Ciptaker Act. The type of research used is normative research, i.e. research with legislative approaches and supporting literature as research source material. The results of the study indicate that (1) the enforcement of the law of illegal fishing in Indonesia as well as enforcing the law on illegal fisheries in Indonesia after the creation of the Ciptaker Act, is basically aimed at protecting fishing resources,ining the sustainability of the marine environment, and ensuring that seafood can be sustainably utilized by future generations. (2) The enforcement of illegal fishing laws in Indonesia after the introduction of the Ciptaker Act, there are some changes in regulations that affect the enforcing of illegal fisheries law in Indonesia.